Are hospitals prepared to support newborn survival? - An evaluation of eight first-referral level hospitals in Kenya. - Opondo, C; Ntoburi, S; Wagai, J; Wafula, J; Wasunna, A; Were, F; Wamae, A; Migiro, S; Irimu, G; English, M (2009)
OBJECTIVE: To assess the availability of resources that support the provision of basic neonatal care in eight first-referral level (district) hospitals in Kenya. METHODS: We selected two hospitals each from four of Kenya's eight provinces with the aim of representing the diversity of this part of the health system in Kenya. We created a checklist of 53 indicator items necessary for providing essential basic care to newborns and assessed their availability at each of the eight hospitals by direct observation, and then compared our observations with the opinions of health workers providing care to newborns on recent availability for some items, using a self-administered structured questionnaire. RESULTS: The hospitals surveyed were often unable to maintain a safe hygienic environment for patients and health care workers; staffing was insufficient and sometimes poorly organised to support the provision of care; some key equipment, laboratory tests, drugs and consumables were not available while patient management guidelines were missing in all sites. CONCLUSION: Hospitals appear relatively poorly prepared to fill their proposed role in ensuring newborn survival. More effective interventions are needed to improve them to meet the special needs of this at-risk group.